Synthesis of Radiopharmaceuticals via “In-Loop” 11C-Carbonylation as Exemplified by the Radiolabeling of Inhibitors of Bruton's Tyrosine Kinase - Donnelly, David J.; Preshlock, Sean; Kaur, Tanpreet; Tran, Tritin; Wilson, Thomas C.; Mhanna, Karim; Henderson, Bradford D.; Batalla, Daniel; Scott, Peter J. H.; Shao, Xia (Frontiers in Nuclear Medicine, 2022)
Positron emission tomography (PET) is an important non-invasive tool to help guide the drug discovery and development process. Positron-emitting–radiolabeled drug candidates represent an important tool for drug hunters to gain insight into a drug's biodistribution and target engagement of exploratory biologic targets of interest. Recently, there have been several drug candidates that incorporate an acryloyl functional group due to their ability to form a covalent bond within the biological target of interest through Michael addition. Methods to incorporate a carbon-11 radionuclide into acrylamide derivatives remain challenging given the reactive nature of this moiety. Herein, we report the improved radiosynthesis of carbon-11–containing acrylamide drug candidates, [11C]ibrutinib, [11C]tolebrutinib, and [11C]evobrutinib, using [11C]CO and a novel “in-loop” 11C-carbonylation reaction. [11C]Ibrutinib, [11C]tolebrutinib, and [11C]evobrutinib were reliably synthesized, generating 2.2-7.1 GBq of these radiopharmaceuticals in radiochemical yields ranging from 3.3 to 12.8% (non-decay corrected; relative to starting [11C]CO2) and molar activities of 281-500 GBq/μmol (7.5-13.5 Ci/μmol), respectively. This study highlights an improved method for incorporating carbon-11 into acrylamide drug candidates using [11C]CO within an HPLC loop suitable for clinical translation using simple modifications of standard automated synthesis modules used for cGMP manufacture of PET radioligands.